1978
DOI: 10.1111/j.1524-4725.1978.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Axillary Hair and Related Phenomena After Removal of Deep Dermal and Subcutaneous Tissue by a Special “Shaving” Technique

Abstract: A subcutaneous tissue "shaver" was used in the treatment of axillary bromhidrosis. Regeneration of axillary hair was observed postoperatively even if subcutaneous tissue and dermis were removed almost up to the level of sebaceous ducts. Hair regenerated more often in male patients whose sebaceous glands and follicular isthmus were designedly left intact than in female patients whose sebaceous glands were designedly removed completely. Some function of apocrine and eccrine glands tends to return over a two-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Complete destruction of the dermal papillae is thought to prevent regrowth of hair. The only two experiences indicating that new papillae may be formed under certain circumstances, are the experiments of Oliver6 in which it was found that vibrissa of rodents may form new dermal papillae if the lower end of the follicle is cut away, and our own findings2,4 that axillary hairs regrow after subcutaneous shaving if the isthmuses and sebaceous ducts of follicles are left intact. Supporting evidence is found in growth of hairs following autotransplantation procedures in which rather superficial flaps of skin from the scalp without deep hair roots had been used to reconstruct excessively small ears (microtia).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Complete destruction of the dermal papillae is thought to prevent regrowth of hair. The only two experiences indicating that new papillae may be formed under certain circumstances, are the experiments of Oliver6 in which it was found that vibrissa of rodents may form new dermal papillae if the lower end of the follicle is cut away, and our own findings2,4 that axillary hairs regrow after subcutaneous shaving if the isthmuses and sebaceous ducts of follicles are left intact. Supporting evidence is found in growth of hairs following autotransplantation procedures in which rather superficial flaps of skin from the scalp without deep hair roots had been used to reconstruct excessively small ears (microtia).…”
Section: Discussionmentioning
confidence: 93%
“…The fact that hairs frequently regrow in spite of supposedly complete destruction of hair roots has been attributed to failure of destruction of dermal papillae in many instances. However, when we found that hairs also regrow after complete removal of the subcutaneous and deep dermal tissue by means of a subcutaneous tissue shaver2, we began to doubt the generally held view that regeneration of hair depends solely on preservation of the dermal hair papillae. Investigation showed that hair may regenerate by new formation in the region of the sebaceous duct (isthmus of the follicle), and there is often new formation of more than one hair per follicle if more than one sebaceous gland is preserved.…”
mentioning
confidence: 95%
“…The pilosebaceous unit is a dynamic structure constantly undergoing cyclic change and endowed with considerable regenerative capacity as seen in wound healing [12] or following partial destruction [15], It sometimes even eliminates its own components in the so-called alarm reaction [20]. Transfollicular extrusion of sebaceous glands was also observed [28], Its participation in the excretion of the foreign material from the dermis was demonstrated experimentally using charcoal particles [7].…”
Section: Discussionmentioning
confidence: 99%
“…Substance P is also an important factor for apocrine sweat production. 71 Capsaicin should be applied once or twice daily for as long as required, but chromhidrosis relapses several days after discontinuation of treatment. 62 BTX-A has also been effective for facial and axillary chromhidrosis.…”
Section: Treatmentmentioning
confidence: 99%
“…[65][66][67][68][69] Three main approaches are possible: removing only subcutaneous tissue without removing skin and with or without axillary superficial fascia removal 70 ; removing skin and subcutaneous tissue en bloc 68 ; and removing skin and subcutaneous tissue en bloc with removing of the adjacent subcutaneous tissue. 51,71 Regeneration of gland function over a period of years may be observed, and this depends mainly on the depth and extension of surgical excision. A novel surgical approach has combined surgical intervention with additional carbon dioxide laser vaporization for the residual apocrine glands.…”
Section: Laboratory Investigationsmentioning
confidence: 99%